The Role of Educational Media in Improving Quality of Human Resources - Muzakkir; Ahdar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Research This about the role of educational media in increase source Power man along acceleration knowledge and technology, hacking impact the more complex learning process because challenge the appear from outside form happen assimilation and acculturation past packages resulting information and communication technology. Whereas from in, occurrence transformation attitude and behavior in demand for child educate. Then global challenges are existing demands for be independent so you can still exist in a competitive era. Phenomenon contemporary describe competition competitive life. In terms of this, that can become proceed is are the people who have source Power reliable human. Demands and pressure people humans to be able to independent or not depends to institutions that can recruiting later after plunge into the world of work. Because remember field Work the narrower and narrower it's overflowing unemployment. Therefore that, deep answer problem this institution competent education in build man own source Power acceptable and marketable. Education is something business build humans to have high intelligence, morals and skills. In the world of education own a number of element important, one of them is media. Media is tool possible communication and information access knowledge to child educate. Succeed whether there is a learning process in the world of education is greatly influenced by the role of the media. However, the role of the media is also influenced by quality and professionalism in play it.